FOR A SERIES OF INDEPENDENT TESTS - Єгоршин, Ю. О.; Красноусова, О. Ю. (Proceedings of National Aviation University, 2021)
Theorems on the probabilities of occurrence of less than three failures for a series of tests under two different conditions, which correspond to different failure probabilities for each test, are proved.